Antioxidant Potential of Raw Meat from Broiler Chicken Fed with Dietary Plant Supplements - Upadhyay, Atul; Katuwal, Nirat; Rai, Basanta Kumar; Shrestha, Srijan; Bhattarai, Rewati Raman; Makise, Tadahiro (2017)
In Nepal, medicinal herbs have traditionally been used to feed animals for growth during illness. This study was conducted to evaluate the antioxidant property of thigh and breast meats obtained from chickens fed with medicinal plants incorporated feeds. Two hundred broiler chickens were randomly assigned to 5 groups. The treatment groups were fed with medicinal herbs supplemented feeds, while the control group was fed with a commercial diet. The aqueous fractions of thigh and breast meats showed significantly higher total phenolic content than control (P=0.05). Among thigh meats, Melochia corchorifolia supplemented feed resulted the highest total phenolic content (109 +-4.5 mg CE/g), followed by Moringa oleifera supplemented one (104 =-5.8 mg CE/g). On carrying our DPPH scavenging activity, thigh meat from chicken fed with Leucaena leucocephala supplemented feed had 45.8% inhibition compared to control (34.7% inhibition). The lipophilic fractions had significantly lower total phenolic content and DPPH scavenging activity. Sensory analyses revealed that meats from chickens fed with Melochia corchorifolia and Alpinia zerumbet hebs had superio flavor, whereash chicken fed with Moringa oleifera had objectionable taste. Poultry feed supplemented with Melochia corchorifolia and Alpinia zerumbet could significantly improve the antioxidant activity and flavor of chicken meat.